Literature Survey of Image Retrieval Using Data Mining Clustering Technique - Saravanan, D; Nandhini, R. Sahaya Nandhini (International Journal of Computer Sciences and Engineering, 2014)
Data mining is the process of extract knowledge from an existing data, among the data sets image data is one is always huge by itself. The usage of this data is increasing rapidly due to his popularity. They are being used in every field today, due to that large amount of data are stored in the database every day. Among such stored data retrieval is not easy; we need a mechanism to group the data’s for fast retrieval. In this paper we discussed some of the existing clustering techniques for clustering the data’s.